Judicial Considerations in Imposing Replacement Money Sanctions in Corruption Cases Involving State Land Transfer - Lameng, Jihan Shavira Yosephin; Elis Rusmiati; Rully Herdita Ramadhani (JUSTISI, 2025)
The study aims to examine and analyze the judge's consideration in the imposition of replacement money in corruption cases involving state land transfer through the lens of justice drawing on progressive legal theory, and the theory of economic analysis of law, while also assesing strategies to maximize the recovery of state financial losses through the application of replacement money. The method of research is normative juridical method with a qualitative descriptive approach, focusing on secondary data such a legislation, court decisions, and legal literature. The research specification used is descriptive analytical. Novelty of this research lies in highlighting analyze the effectiveness of additional criminal sanctions in the form of replacement money in corruptions offenses involving state land transfer in optimizing the recovery of state finansial losses through progressive law theory and economic analysis of law approach. The Results indicate that the implementation of replacement money as an additional criminal sanctions is considered not to be optimal in maximizing the recovery of state financial losses, Judges' considerations in several decisions examined show that the imposition of replacement money has not implemented progressive legal theory, without considering other forms of losses impacted by corruption offenses involving state land transfer. This is due to the absence of parameters as guidelines in imposing of replacement money Conclusion, it can be known that although Article 18 paragraph (1) letter (b) of the Corruption Law has included the amount of replacement money payments balanced with the assets/objects obtained from corruption crimes, a more progressive approach are needed to ensure that the imposition of replacement money can effectively restore the state's financial losses. Therefore, it is necessary to calculate the amount of replacement money using the NJOP indicator in corruption cases involving state land transfer in line with efforts to optimize the return of state financial losses.